Design of Noise-Reducing Two-Stage Cage Control Valve and Its Fluid Characteristics and Cavitation Study - Ruiming Yu; Xi Lu (Journal of Chemistry)
For all kinds of media noise, noise reduction valve cage cannot meet the equal percentage flow characteristics, and for manufacturing and processing and other technical problems, research and design of new noise reduction two-stage cage control valve are necessary. The valve adopts noise reduction valve cage and curve valve cage with noise reduction, forming a two-stage noise reduction, with uniform flow, diffusion, and noise reduction effect, to meet the regulating valve equal percentage flow characteristics. The spool is evenly stressed and not easy to loosen and fall off, and the small opening is not easy to vibrate and shake. The flow characteristics of the noise-reducing two-stage cage control valve are studied, and the fluid flow coefficients, flow characteristic curves, the relationship of flow coefficients with nominal diameter at the same stroke, and the relationship of flow coefficients with different nominal diameters at different strokes are analyzed. The relationship between nominal diameter constant opening and cavitation coefficient with inlet velocity, the relationship between inlet velocity and cavitation coefficient with nominal diameter at half opening, and the relationship between inlet velocity and cavitation coefficient with nominal diameter at full opening were studied, and the cavitation generation and its effect on noise were analyzed. The noise and cavitation test showed that noise is very small and cavitation is difficult to produce, all meeting the noise reduction requirements.